Design of Low Inductance SiC-MOS/Si-IGBT Hybrid Module for PV Inverters - Ye Wang; Min Chen; Dehong Xu (IEEE Open Journal of Power Electronics, 2022)
In this paper, design of a low parasitic inductance T-type SiC-MOS/Si-IGBT hybrid module for PV inverters is studied. Current commutation loops and self- and mutual inductances model of the hybrid module are analyzed. Then stacked substrates structures with vertical power commutation loop to reduce parasitic inductance are identified and compared. Finally, a hybrid module with stacked bond wire substrates structure is built and test results are provided to verify the design.